2017
DOI: 10.21123/bsj.2017.14.4.0713
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Level of some Adipokines in Hypo-and Hyperthyroids Patients in Baghdad City

Abstract: In the early 90s military operations and United Nations Special Commission "UNSCOM" teams have been destroyed the past Iraqi chemical program. Both operations led an extensive number of scattered remnants of contaminated areas. The quantities of hazardous materials, incomplete destructed materials, and toxic chemicals were sealed in two bunkers. Deficiency of appropriate destruction technology led to spreading the contamination around the storage site. This paper aims to introduce the environmental detection o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In the case of patients with overt hypothyroidism, subclinical hypothyroidism, and normal thyroid function, there were no differences in vaspin levels among the groups; additionally, there was no correlation between vaspin and thyroid-stimulating hormone (TSH), T3, or T4 levels [75], but the limitation of the study was the small sample size. Moreover, some research showed that in patients with hypothyroidism, the level of vaspin in serum was significantly increased, whereas in patients with hyperthyroidism, it was significant decreased compared with the control group [76]. The observed differences between studies may be dependent on the patients' origins.…”
Section: Vaspin Expression and Action In The Thyroid Glandmentioning
confidence: 98%
See 1 more Smart Citation
“…In the case of patients with overt hypothyroidism, subclinical hypothyroidism, and normal thyroid function, there were no differences in vaspin levels among the groups; additionally, there was no correlation between vaspin and thyroid-stimulating hormone (TSH), T3, or T4 levels [75], but the limitation of the study was the small sample size. Moreover, some research showed that in patients with hypothyroidism, the level of vaspin in serum was significantly increased, whereas in patients with hyperthyroidism, it was significant decreased compared with the control group [76]. The observed differences between studies may be dependent on the patients' origins.…”
Section: Vaspin Expression and Action In The Thyroid Glandmentioning
confidence: 98%
“…The data describing vaspin function in ovarian and testicular cells will be useful to regulate agricultural species, including pigs breeding. Finally, some authors indicated vaspin as a clinical predictor and novel biomarker of many pathologies, including GDM, PCOS [13], MetS [89], hypo-and hyperthyroidism [76], MTC [106], and semen quality [86].…”
Section: Perspectivesmentioning
confidence: 99%